Eosinophilic fasciitis: an atypical presentation of a rare disease - Cabral,Catia (2019)
SUMMARY Eosinophilic fasciitis, or Shulman's disease, is a rare disease of unknown etiology. It is characterized by peripheral eosinophilia, hypergammaglobulinemia, and high erythrocyte sedimentation rate. The diagnosis is confirmed by a deep biopsy of the skin. The first line of treatment is corticotherapy. We present a rare case of eosinophilic fasciitis in a 27-year-old woman with an atypical presentation with symmetrical peripheral edema and a Groove sign. The patient responded well to treatment with corticosteroids at high doses and, in this context, was associated with hydroxychloroquine and azathioprine. After two and a half years, peripheral eosinophilia had increased, and more of her skin had hardened. At that time, the therapy was modified to include corticoids, methotrexate, and penicillamine. It is of great importance to publicize these cases that allow us to gather experience and better treat our patients.